2015
DOI: 10.1140/epjp/i2015-15103-8
|View full text |Cite
|
Sign up to set email alerts
|

Regular and chaotic vibration in a piezoelectric energy harvester with fractional damping

Abstract: Abstract. We examine a vibrational energy harvester consisting of a mechanical resonator with a fractional damping and electrical circuit coupled by a piezoelectric converter. By comparing the bifurcation diagrams and the power output we show that the fractional order of damping changes the system response considerably and affects the power output. Various dynamic responses of the energy harvester are examined using phase trajectory, Fourier spectrum, Multi-scale entropy and 0-1 test. The numerical analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It has been found that in many practical cases, systems can be more adequately described using fractional-order differential equations [1][2][3][4][5][6][7][8][9][10][11]. Furthermore, fractional-order derivatives are excellent instruments for the description of memory and hereditary properties of various materials and processes [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that in many practical cases, systems can be more adequately described using fractional-order differential equations [1][2][3][4][5][6][7][8][9][10][11]. Furthermore, fractional-order derivatives are excellent instruments for the description of memory and hereditary properties of various materials and processes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in the context of broadband energy harvesting, bifurcations and chaotic vibrations have been studied in several papers. Cao et al [6,7] studied chaos in the fractionally damped broadband piezoelectric energy generator in a system with additional magnets. Syta et al [8] analysed the dynamic response of piezoelectric material attached to a bistable laminate plate.…”
Section: Introductionmentioning
confidence: 99%
“…Ordinarily, the possible mechanisms for harvesting ambient energy include electromagnetic mechanism [3,4], piezoelectric mechanism [5,6], pyroelectric mechanism [7,8] and electrostatic mechanism [9,10]. The fundamental principle of the electromagnetic energy harvester can be boiled down to the law of electromagnetic induction.…”
Section: Introductionmentioning
confidence: 99%